Association between Lactobacillus plantarum consumption and diabetic dermatopathy: a case-control study - Arroyo, Jose J. Alvarez; Hernandez Sanchez, Irvin (International Journal of Research in Dermatology, 2025)
Background: Diabetic dermatopathy (DD) is a common skin complication in patients with type 2 diabetes mellitus, associated with microvascular alterations. Its treatment is limited, but probiotics such as Lactobacillus plantarum have shown potential in modulating inflammation and improving skin health. This study evaluated the association between Lactobacillus plantarum consumption and the presence of DD. Methods: A case-control study was conducted with 150 patients recruited at Ticomán hospital, Mexico City. Cases included 50 patients with a clinical diagnosis of DD, while controls comprised 100 patients without evidence of the condition, matched by age and sex. Lactobacillus plantarum consumption was assessed through structured questionnaires and medical history reviews. Data were analyzed using logistic regression models to calculate odds ratios (OR) and 95% confidence intervals (95% CI). Results: Lactobacillus plantarum consumption was less frequent in cases (20%) than in controls (30%). Analyses indicated a significant association between Lactobacillus plantarum consumption and a lower likelihood of developing DD (adjusted OR=0.60; 95% CI=0.37-0.97; p=0.034). Conclusions: The consumption of Lactobacillus plantarum is associated with a lower likelihood of developing DD in patients with type 2 diabetes mellitus. These findings highlight the potential of probiotics as a non-invasive preventive intervention in this population.